Unsteady Separated Stagnation-Point Flow with Suction towards a Stretching Sheet - Lok, Yian Yian; Ahmad , Syakila; Pop, Ioan (AIP Publishing, 2014)
The problem of unsteady boundary layer separated stagnation-point flow towards a porous stretching sheet is considered. By using a similarity transformation, the governing equations are reduced to a system of ordinary differential equations which are then solved numerically. The effects of suction and stretching parameters on the flow characteristics are studied. It is observed that the solutions admit two types of solutions, one is the attached flow solution and the other is reverse flow solution.